A plum-pudding like mesoporous SiO2/flake graphite nanocomposite with superior rate performance for LIB anode materials1. Issue 35 (21st September 2015) - Li, Huan-Huan; Zhang, Lin-Lin; Fan, Chao-Ying; Wang, Kang; Wu, Xing-Long; Sun, Hai-Zhu; Zhang, Jing-Ping
<x xml:space="preserve">Abstract</x> A novel kind of plum-pudding like mesoporous SiO2 nanospheres (MSNs) and flake graphite (FG) nanocomposite (pp-MSNs/FG) was designed and fabricated via a facile and cost-effective hydrothermal method.